2006
DOI: 10.1183/09031936.06.00143905
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of nitrogen dioxide on mortality: an analysis within the APHEA project

Abstract: The short-term effects of nitrogen dioxide (NO 2 ) on total, cardiovascular and respiratory mortality in 30 European cities participating in the Air Pollution on Health: a European Approach (APHEA)-2 project were investigated.The association was examined using hierarchical models implemented in two stages. In the first stage, data from each city were analysed separately, whereas in the second stage, the cityspecific air pollution estimates were regressed on city-specific covariates to obtain overall estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
165
8
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(188 citation statements)
references
References 41 publications
14
165
8
1
Order By: Relevance
“…Two pollutant models suggested that the observed association of UFP NC with mortality was not confounded by NO, NO 2 , or CO. Other studies noted that NO 2 might serve as a surrogate of other unmeasured pollutants like UFP (Samoli et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Two pollutant models suggested that the observed association of UFP NC with mortality was not confounded by NO, NO 2 , or CO. Other studies noted that NO 2 might serve as a surrogate of other unmeasured pollutants like UFP (Samoli et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have shown consistent associations of long-term NO 2 exposure with decreased lung function and increased risk of respiratory symptoms [Ackermann-Liebrich et al, 1997;Schindler et al, 1998;Panella et al, 2000;Smith et al, 2000;Gauderman et al, 2000Gauderman et al, , 2002. Strong associations exist between NO 2 and nonaccidental mortality in daily time series studies [Steib et al, 2003;Burnett et al, 2004;Samoli et al, 2006]. NO 2 concentrations are also highly correlated with other pollutants either emitted by the same sources or formed through complex reactions in the atmosphere [e.g., Brook et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Th e same conclusion was made by the authors of a systematic review and meta-analysis of global association of air pollut- ants and heart failure 27 . Nitrogen dioxide is a primary pollutant and strong respiratory irritant mainly from outdoor sources including motor vehicles and fossilfuel power plants, whereas the most important indoor sources are gas heaters, stoves and tobacco smoke 28 . Th e number of patients admitted to ED correlates with the concentration of NO 2 and PM 10 particles 8,10,24,[29][30][31] , which have strong infl uence on cardiovascular morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, air pollution poses a great health risk even in developed countries with legally defi ned thresholds of air pollution [4][5][6] . Air pollution is associated with an increased risk of various types of cardiac arrhythmias [7][8][9][10][11] , as a consequence of changes in the automation or conduction of impulses that can occur in all parts and systems of the heart 12 .…”
Section: Introductionmentioning
confidence: 99%